The Titanic secret [large type] - Cussler, Clive; Du Brul, Jack B (Cussler, Clive. Isaac Bell novels, 2019)
A century apart, Dirk Pitt and Isaac Bell team up to unlock the truth about the most famous maritime disaster of all time. In the present day, Dirk Pitt must make a daring rescue from inside an antiquated submersible in the waters around New York City. His reward afterwards is a document left behind a century earlier by legendary detective Isaac Bell--a document that re-opens a historical mystery... In 1911 Colorado, Isaac Bell is asked to look into an unexplained tragedy at Little Angel Mine, a disaster in which nine people died. His dangerous quest to answer that riddle leads to a larger one centered on a rare element with extraordinary powers and of virtually incalculable value. As he discovers that there are people who will do anything to control the substance, Isaac Bell will find out how far he'll go to stop them.--